2020
DOI: 10.4103/ajns.ajns_117_20
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic third ventriculostomy in failed ventriculoperitoneal shunt in pediatric population

Abstract: Introduction: Ventriculoperitoneal (VP) shunt malfunction is common in pediatric age group patients. There is a high complication rate and revision rate of VP shunt. Endoscopic third ventriculostomy (ETV) can alleviate these complications and can act as an effective alternative for the treatment of hydrocephalus in this age group of patients. Materials and Methods: The authors retrospectively reviewed the management and outcome of 36 failed VP shunts in pediatric patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Failures can also occur in high protein and fibrinogen concentration cases, as in cases of infection or post-ventricular bleeding. Fukuhara found that preoperative infections are a high-risk factor for third ventriculocisternostomy failure, as only 11.1% of patients with meningitis remained symptom-free after five years of follow-up (Al-Hakim et al, 2019;Choudhary et al, 2020;Gonzalez-Argote, 2022;Mbaye et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Failures can also occur in high protein and fibrinogen concentration cases, as in cases of infection or post-ventricular bleeding. Fukuhara found that preoperative infections are a high-risk factor for third ventriculocisternostomy failure, as only 11.1% of patients with meningitis remained symptom-free after five years of follow-up (Al-Hakim et al, 2019;Choudhary et al, 2020;Gonzalez-Argote, 2022;Mbaye et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Some previous studies have shown a significant effect of age, 5 whereas others have shown no significant effect of age on outcome. 11,18 Similarly, the etiology of hydrocephalus has had a significant effect on outcome in some studies, 15,17 but not in others. 11 One possible explanation for the lack of significance in the present study is the lack of variation in the sample for these two components of the ETVSS.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also shown an association between a history of multiple shunt revisions and lower likelihood of success of postshunt ETV. 13,15,16 Our analysis of this risk factor was limited to a subset of the overall sample: those patients for whom the details of all previous shunt surgeries were known. However, in that subset we saw no association between number of shunt revisions and postshunt ETV success.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation